Adverse drug reactions after intravenous rituximab infusion are more common in hematologic malignancies than in autoimmune disorders and can be predicted by the combination of few clinical and laboratory parameters: results from a retrospective, multicenter study of 374 patients. Issue 11 (2nd November 2017) - D'Arena, Giovanni; Simeon, Vittorio; Laurenti, Luca; Cimminiello, Michele; Innocenti, Idanna; Gilio, Michele; Padula, Angela; Vigliotti, Maria Luigia; De Lorenzo, Sonya; Loseto, Giacomo; Passarelli, Anna; Di Minno, Matteo Nicola Dario; et al.
Abstract: Rituximab is an effective treatment for CD20 + B-cell malignancies and autoimmune disorders. However, adverse drug reactions (ADRs) may occur after rituximab infusion, causing, in rare cases, its discontinuation. In this multicenter, retrospective study, among 374 patients treated with rituximab i.v., 23.5% experienced ADRs. Mean follow-up was 20.6 months (range 8–135). Overall, ADRs were significantly more frequent in non-Hodgkin lymphomas (NHL) and chronic lymphocytic leukemias (25–35.9%), than in autoimmune diseases (9.4–17.5%) ( p  < .0001). Grade 3–4 toxicity was observed in eight patients (2.1%), and in four of them (1% of all patients) definitive drug discontinuation was necessary. Interestingly, three groups of patients with different risk of developing ADR were identified, according to a predictive heat-map developed combining four parameters (splenomegaly, history of allergy, hemoglobin levels and gender) selected by multivariate analysis. This model may be useful in identifying patients at higher risk of ADRs, needing appropriate preventing therapies.